‘Bosons’ and ‘fermions’ in social and economic systems - Rashkovskiy, Sergey A. (Physica A, 2019)
We analyze social and economic systems with a hierarchical structure and show that for such systems, it is possible to construct thermostatistics, based on the intermediate Gentile statistics. We show that in social and economic hierarchical systems there are elements that obey the Fermi–Dirac statistics and can be called fermions, as well as elements that are approximately subject to Bose–Einstein statistics and can be called bosons. We derive the first and second laws of thermodynamics for the considered economic system and show that such concepts as temperature, pressure and financial potential (which is an analog of the chemical potential in thermodynamics) that characterize the state of the economic system as a whole, can be introduced for economic systems •Statistical description of hierarchical social and economic systems is proposed.•In social and economic hierarchical systems, there are elements that obey the quantum ststistics.•The social and economic hierarchical systems can be described by the Gentile statistics.•The first and second laws of thermodynamics are derived for economic system.